Long-memory versus structural breaks: An overview - Philipp Sibbertsen (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2001)
We discuss the increasing literature on misspecifying structural breaks or more general trends as long range dependence. We consider tests on structural breaks in the long-memory regression model as well as the behaviour of estimators of the memory parameter when structural breaks or trends are in the data but long-memory is not. It can be seen that it is hard to distinguish deterministic trends from long-range dependence.
Keywords: 519; Long memory; structural breaks; trends; Zeitreihenanalyse; Strukturbruch; Theorie